Political attention, collaborative governance and adaptive capacity in flood risk mitigation within municipal administrations - Becker, Per ; 0000-0001-9379-9461; Cedergren, Alexander; Hassel, Henrik (UKADR conference 2024, London, United Kingdom, 2024-06-26 - 2024-06-27, 2024)
Flood risk mitigation requires collaborative governance that involves many and diverse actors. The capacity of municipal administrations to anticipate and adapt plays a crucial role in addressing flood risk in the Nordic region. However, although flood risk often spans boundaries, each organisation's governance capacity depends largely on the formation of collaborative ties among involved politicians and civil servants, making it vital to understand the underlying processes driving such tie formation. Utilising a comparative approach, this study investigates the impact of political attention to flood risk mitigation on the formation of collaborative ties among individuals contributing to flood risk mitigation in their daily work. The results show that political attention, conceptualised as issue saliency and a broad problem framing, has a marked effect on these processes. Politicians, high-level managers and planners increase their relative efforts in building relationships if the political attention is high, ending the dominance of water & sewage experts when political attention is low. Further, political attention is also positively associated with the abilities of appointed coordinators to engage others in collaborative relationships. Further research is needed to better understand the studied nexus, and to address lasting methodological challenges.
Keywords: collaborative governance; flood risk; Exponential random graph model (ERGM); social network analysis